2012
DOI: 10.4315/0362-028x.jfp-11-399
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal of Salmonella Typhimurium by Rain Splash onto Tomato Plants

Abstract: Outbreaks of Salmonella enterica have increasingly been associated with tomatoes and traced back to production areas, but the spread of Salmonella from a point source onto plants has not been described. Splash dispersal by rain could be one means of dissemination. Green fluorescent protein–labeled, kanamycin-resistant Salmonella enterica sv. Typhimurium dispensed on the surface of plastic mulch, organic mulch, or soil at 108 CFU/cm2 was used as the point source in the center of a rain simulator. Tomato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(61 citation statements)
references
References 39 publications
1
59
1
Order By: Relevance
“…Previous studies have also shown that storms and rain can increase produce contamination (34)(35)(36). These studies identified that rain splashed Salmonella Typhimurium onto tomato plants (34), splashed Colletotrichum acutatum onto strawberry fruits (36), and led to the transport of Salmonella Typhimurium to tomato fruits by aerosols (35). A modeling study showed that the probability of lettuce contamination with E. coli O157:H7 from manureamended soil was significantly correlated with the number of times it rained (37).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also shown that storms and rain can increase produce contamination (34)(35)(36). These studies identified that rain splashed Salmonella Typhimurium onto tomato plants (34), splashed Colletotrichum acutatum onto strawberry fruits (36), and led to the transport of Salmonella Typhimurium to tomato fruits by aerosols (35). A modeling study showed that the probability of lettuce contamination with E. coli O157:H7 from manureamended soil was significantly correlated with the number of times it rained (37).…”
Section: Discussionmentioning
confidence: 99%
“…However, the recovery of the inoculated E. coli in soil from both surface and subsurface samples at the 9-m distance provides strong evidence for the subsurface lateral transport of E. coli contributing to the contamination of spinach foliar tissue at that distance. Rain splash of contaminated soil onto the spinach leaves during the heavy rainfall in the first few days after the initial flooding event may be the cause of the recovery of E. coli from the spinach leaves as rain splash has been shown to be a significant method of dispersal of bacteria in soil to plant tissue (16).…”
Section: Discussionmentioning
confidence: 99%
“…Plastic mulch prevents direct contact of tomato fruits with foodborne pathogencontaminated soil (Guo et al, 2002a) but has the potential to enhance splash dispersal by rain or irrigation water. Cevallos-Cevallos et al (2012a) demonstrated that Salmonella may be dispersed by rain to contaminate tomato plants in the field, especially during rain showers of 10 minutes or more and when plastic mulch is used. They concluded that this was probably due, in part, to the different moisture levels on the tomato surface as both plastic and organic mulch stayed wet for at least 24 h after the rain, whereas soil dried within this time.…”
Section: Climatic Conditionsmentioning
confidence: 99%